Important of prerequisites for successful collective bargaining - Maulad Bahrol, Khadijah; Raja Mohd Rasi, Raja Zuraidah; Ismail, Fadillah; Tasmin, Rosmaini (Penerbit Uthm, 2019)
Collective bring out the meaning of group while bargaining is the negotiation which include terms and any transaction whereby for this topic collective bargaining can be define as something that refers to the actual process such as the worker gather and together start to bargain or make a deal with management on the key of term and condition that are stated in the employment act. Some association which is any business relationship direct which is simply the workers separately advocate while associations advocate for themselves by control work costs and augment representative adequacy. There are additionally association which is the outsider arranges different terms and states of work in the interest of numerous representatives at one time and this is known as aggregate dealing. The outsider attempting to speak to numerous representatives altogether is known as a worker's organisation (Collins, 2018).